Rancang Bangun Ergonomi Portabel Floor Chair Sebagai Sarana Penunjang Aktivitas Pondok Pesantren - Hikmah Wijayanti; Tri Andi Setiawan; Fais Hamzah (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Until now, the Ministry of Religion (Kemenag) has recorded that the number of Islamic boarding schools in Indonesia is 26,975 units as of April 2022. All of these Islamic boarding schools educate as many as 2.65 million students. With a number that is not small, it is not uncommon for an Islamic boarding school to experience problems in providing learning facilities such as tables and chairs. This makes most of the learning activities in the boarding house carried out by sitting on the floor. As a result, these habits have an adverse effect on the health of the students. These problems were reviewed using the Gotrak questionnaire and the RULA (Rapid Upper Limb Assessment) method. From the results of the preliminary study, it was known that many students complained of frequent aches or pain in the neck, back, hips and legs. And from the RULA method it shows a score of 5 which means moderate risk and further treatment is needed. From these problems, the idea was generated to make an ergonomic and portable floor chair. To solve this problem, product design and development will be carried out using the Ulrich method. The dimensions of this chair are 64 cm long, 42 cm wide,41 cm high when used on the cross-legged table, and 68 cm maximum height when sitting on a chair. In the test, the RULA score was 2, which means moderate risk and further treatment is needed with a total budget required of IDR 647.100,-